Genotyping methods for monitoring the epidemic evolution of A. baumannii strains - Salman Shaheer Ahmed; Emine Alp (Journal of Infection in Developing Countries)
Acinetobacter baumannii is clustered with other phenotypically similar species into what has commonly become known as the ACB complex: A. calcoaceticus, A. pittii and, A. nosocomialis. The ecology and pathology of most of these species are not well understood, mainly because current specific phenotypic techniques have, to date, been insufficient. This has inhibited both the precise identification of, as well as the ability to discriminate between, these clinically important and closely related Acinetobacter strains.  However, new genotypic methods have greatly enhanced our capacity to identify the ACB complex. This has resulted in the implementation of more rational infection control programs. Several genotypic identification methods are explored in this study, including non-polymerase chain reaction (PCR)-based and PCR-based methods. These methods include ribotyping, pulsed-field gel electrophoresis, 16S rRNA identification, multilocus sequence typing, single locus sequence typing, restriction fragment length polymorphism analysis, restriction analysis of 16S-23S rRNA intergenic spacer sequences, rapid amplification of polymorphic DNA, and repetitive extragenic palindromic PCR; however, there is no current single ideal genotyping method. Each one has its own advantages and disadvantages. With this in mind we reviewed current and new genotyping methods used to characterize the Acinetobacter species.